PENGARUH INDEPENDENSI, INTEGRITAS, BUDAYA KERJA, KECERDASAN EMOSIONAL DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR KANTOR AKUNTAN PUBLIK (KAP) DI MAKASSAR - Arman S Arman S (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The effect of independency, integrity, work culture ,emotional intelligence and leadership style of auditor performance at Public Accounting Firm (KAP) in Makassar. (supervised by Muhammad Su'un, FadliahNasaruddin).This research aimsat examining the influence of independency, integrity, work culture, emotional intelligence, and leadership style ofauditor's performance. This research using primary data obtained by questionnaire, data were collected using survey method with questionnaire form. Samples of this research are the auditor who is at Public Accounting Firm (KAP) in Makassar. Data were analyzed by Statistical Package For The Social Sciences (SPSS).The results of this research show that auditor independency, Integrity, Work Culture, Emotional Intelligence and Leadership style gave a positive effect on auditor performance. The result of hypothesis testing provide synthesis that higher independence of auditors, Integrity, Work Culture, Emotional Intelligence and Leadership Style owned by auditor at KAP, then performance of auditors will be better also.